Confronting rape and sexual assault - Odem, Mary E.; Clay-Warner, Jody (Worlds of women, 1998)
I. Speaking out. Rape poem / Marge Piercy -- Surviving rape : a morning/mourning ritual / Andrea Benton Rushing -- Rape sonnets / Andi Rosenthal -- Mikvah ceremony for Laura / Laura Levitt and Sue Ann Wasserman. II. Defining the problem. A feminist redefinition of rape and sexual assault : historical foundations and change / Patricia L.N. Donat and John D'Emilio -- Hidden rape : sexual aggression and victimization in a national sample of students in higher education / Mary P. Koss -- Wife rape and the law / Diana E.H. Russell -- The effects of sexual assault on men : a survey of twenty-two victims / Gilliam Mezey and Michael King. III. Why rape happens. The socio-cultural context of rape : a cross-cultural study / Peggy Reeves Sanday -- "Riding the bull at Gilley's" : convicted rapists describe the rewards of rape / Diana Scully and Joseph Marolla -- Rape myths / Martha R. Burt -- Sexual aggression, masculinity, and fathers / David Lisak